SeqX: a tool to detect, analyze and visualize residue co-locations in protein and nucleic acid structures - Fördös Gergely; Biro Jan C (BMC Bioinformatics, 2005)
Abstract Background The interacting residues of protein and nucleic acid sequences are close to each other – they are co-located. Structure databases (like Protein Data Bank, PDB and Nucleic Acid Data Bank, NDB) contain all information about these co-locations; however it is not an easy task to penetrate this complex information. We developed a JAVA tool, called SeqX for this purpose. Results SeqX tool is useful to detect, analyze and visualize residue co-locations in protein and nucleic acid structures. The user a. selects a structure from PDB; b. chooses an atom that is commonly present in every residues of the nucleic acid and/or protein structure(s) c. defines a distance from these atoms (3–15 Å). The SeqX tool detects every residue that is located within the defined distances from the defined "backbone" atom(s); provides a DotPlot-like visualization (Residues Contact Map), and calculates the frequency of every possible residue pairs (Residue Contact Table) in the observed structure. It is possible to exclude +/- 1 to 10 neighbor residues in the same polymeric chain from detection, which greatly improves the specificity of detections (up to 60% when tested on dsDNA). Results obtained on protein structures showed highly significant correlations with results obtained from literature (p < 0.0001, n = 210, four different subsets). The co-location frequency of physico-chemically compatible amino acids is significantly higher than is calculated and expected in random protein sequences (p < 0.0001, n = 80). Conclusion The tool is simple and easy to use and provides a quick and reliable visualization and analyses of residue co-locations in protein and nucleic acid structures. Availability and requirements http://janbiro.com/Downloads.html SeqX, Java J2SE Runtime Environment 5.0 (available from [see <supplr sid="S1">Additional file 1</supplr>] http://www.sun.com) and at least a 1 GHz processor and with a minimum 256 Mb RAM. Source codes are available from the authors. <suppl id="S1"> Additional File 1 <text> SeqX_1.041_05601.jar. see this article </text> <file name="1471-2105-6-170-S1.jar"> Click here for file </file> </suppl>